Impaired p53/CEP‐1 is associated with lifespan extension through an age‐related imbalance in the energy metabolism of C. elegans. (8th November 2017) - Yanase, Sumino; Suda, Hitoshi; Yasuda, Kayo; Ishii, Naoaki
Abstract : In the nematode Caenorhabditis elegans, the mammalian tumor suppressor p53 ortholog CEP‐1 mediates the stress response, activates germ line apoptosis and regulates meiotic chromosome segregation. A reduction in its expression, which frequently occurs in mammalian cancer cells, extends lifespan and induces an adaptive response in C. elegans . However, these effects do not involve an increase in oxidative stress resistance. Here, we showed that intermittent exposure to hyperoxia, which induces oxidative stress resistance and lowers the production of ROS derived from mitochondrial respiration in C. elegans, slightly improved the lifespan extension of cep‐1 mutant. Interestingly, ATP levels were increased without an increase in oxygen consumption in cep‐1 mutant during aging. In the wild‐type, lactate levels and consequentially the lactate/pyruvate ratio decreased during aging in adults. Furthermore, the expression levels of mitochondrial respiration‐related sco‐1, which is a target of p53/CEP‐1, as well as those of gluconeogenesis regulation and mammalian sirtuin ortholog genes, were also increased in the aged and adaptive conditioned wild‐type animals. In contrast, the lactate/pyruvate ratio increased in cells of the cep‐1 mutant and was amplified by intermittent hyperoxia. These results suggest that impaired p53/CEP‐1 leads to an imbalance in the age‐related energy metabolic alteration between mitochondrial oxidative phosphorylation and aerobic glycolysis and plays an important role in the extension of both intact and adaptive lifespans. Abstract : Here, we examined that intermittent exposure to hyperoxia slightly improved the lifespan extension of cep‐1 mutant, which deletes the mammalian tumor suppressor p53 ortholog gene, and found that the ATP levels were increased without an increase in oxygen consumption in cep‐1 mutant during aging. In the wild‐type, expression of sco‐1 gene that is a target of p53/CEP‐1 increased, and lactate levels and consequentially the lactate/pyruvate ratio decreased during aging. These results suggest that impaired p53/CEP‐1 leads to an imbalance in the age‐related energy metabolic alteration between mitochondrial oxidative phosphorylation and aerobic glycolysis and plays an important role in the extension of both intact and adaptive lifespans.